Pyrazine-based organic electrode material for high-performance supercapacitor applications. (April 2022) - Biradar, Madan R.; Salkar, Akshay V.; Morajkar, Pranay P.; Bhosale, Sheshanath V.; Bhosale, Sidhanath V.
Highlights: Synthesis of naphtho[2, 3-h]naphtho[2′, 3′:5, 6]quinoxalino[2, 3-a]naphtho[2′, 3′:5, 6] quinoxaline[2, 3-c]phenazine-5, 12, 17, 22, 27, 30-hexaone (Pyz-ANQ ). Pyz-ANQ based electrode materials successfully applied for the supercapacitor applications. Pyz-ANQ/ CP shows highest specific capacitance 85.2 f g -1 (CV) and 43.1 f g -1 (GCD). Pyz-ANQ/ CP based symmetric solid-state two-electrode SCs showed specific capacitance by two methods CV and GCD such as 52.5 f g -1 @ 5 mV s -1 and 36.6 f g -1 @ 0.5 a g -1 . Pyz-ANQ/ CP shows excellent cyclic performance in three electrode and two electrode system in the percentage of 78.8% and 75.9% for 2000 GCD cycles. Abstract: Pseudocapacitors ( P Cs) exhibit high capacitance and high energy density, which renders incredible execution in energy storage gadgets. P Cs bridge the gap between batteries and electrostatic double-layer capacitors (EDLCs). Herein, we designed novel electrode material i.e. naphtho[2, 3-h]naphtho[2′, 3′:5, 6]quinoxalino[2, 3-a]naphtho[2′, 3′:5, 6]quinoxaline [2, 3-c]phenazine-5, 12, 17, 22, 27, 30-hexaone (Pyz-ANQ ) composed of hexaketocyclohexane (HKCH) and 2, 3-diaminoanthraquione (ANQ) subunits. The Pyz-ANQ electrode has been fabricated on a Toray carbon paper (CP) and used as a pseudocapacitor electrode which showed efficient pseudocapacitor performance in a three-electrode configuration. The specific capacitance ( Csp ) by cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) analysis are 85.2 F g −1 at a scan rate of 5 mV s −1 and 43.1 F g −1 at current density 0.5 A g −1 in 1 M H2 SO4, respectively. The P Cs behavior is attributed to the reversible redox chemistry of Pyz-ANQ . Furthermore, we fused the material into a symmetric solid-state two-electrode supercapacitor (SSSC) device for practical demonstration of its potential in future energy storage applications and it shows the Csp value by two methods CV and GCD such as 52.5 F g −1 @ 5 mV s −1 and 36.6 F g −1 @ 0.5 A g −1, as well as it shows excellent cyclic performance in three-electrode and two-electrode system in the percentage of 78.8% and 75.9% for 2000 GCD cycles. Significantly, Pyz-ANQ/CP electrode has an energy density of 2.6 Wh kg −1 at 4.7 kW kg −1 of power density, respectively. In this way, by utilizing HKCH and ANQ in the redox system, Pyz-ANQ/CP results in pseudocapacitive energy storage, bringing a new dimension to improve the chemistry of organic supercapacitors. Graphical abstract: Image, graphical abstract